Analysis and Optimization of Telkomsel Coverage Signals for the London Sumatra Plantation Company - Akhmad Sayuti; Serry Davizan; Irwansyah (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
With the advancement of plantations in South Sumatra in particular and Indonesia in general. So, there is a lot of opening up of new plantation land, be it oil palm, rubber and other plantations. Therefore, Telkomsel is always at the forefront by adding new BTS (Base Transceiver Station). Telkomsel always provides comfort to its users to continue trying to maintain signal stability so that customers continue to experience satisfactory results. One of them is the London Sumatra Plantation Company, an oil palm plantation company located in Musi Banyuasin Regency. The checks in this research used the Drive test method using TEMS Investigation 11.0.1. At the beginning of checking the location, the BTS that covered the London Sumatra Group Plantation Company building was BinaKahuripan, a distance of ± 10KM, while apart from this BTS there was a BTS that was closer, namely SungaiKubu, ± 6KM. After analysis, the reason why the SungaiKubu BTS is not dominant is because the antenna direction is not pointing towards the London Sumatra Group location, which causes the dominant BTS to be BinaKahuripan. So, from the results of this analysis, a solution was produced, namely Reorienting the SungaiKubu BTS antenna from Directional. Previously 330º was changed to 355º as well as for mechanical & electrical from 2 & 3, changed to all 1. From the results of the antenna reorientation, the SungaiKubu BTS has become more dominant. Checks were carried out in 2 positions, namely Position 1 and Position 2. The results of the checks produced an average Rx Level value for Position 1 before the antenna reorientation was -94.4 dBm while after the antenna reorientation was -81 dBm. The average Rx Quality value before the antenna reorientation was 3.8 while after the antenna reorientation was 2. The results of checking the average Rx Level for Position 2 before the antenna reorientation was -89 dBm while after the antenna reorientation was -81 dBm. The average Rx Quality value before antenna reorientation was 4.9 while after antenna reorientation was 2.